The Role of Malondialdehyde (MDA) and Ferric Reducing Antioxidant Power (FRAP) in Patients with Hypertension - Alam, Rohsan; Ahsan, Haseeb; Khan, Saba (Molecular and Cellular Biomedical Sciences, 2023)
Oxidative stress contributes to the pathogenesis of hypertension and studies have shown that hypertension is associated with an increase in oxidative stress. Reactive oxygen species (ROS) lead to hypertension and antioxidants may be beneficial for its prevention. The main cause of oxidative stress in hypertension is endothelial dysfunction due to the malfunctions in the vasodilator systems, specifically the molecular mechanism of ROS and nitric oxide (NO). The level of malondialdehyde (MDA), a biomarker of lipid peroxidation and oxidative stress, is found to be higher in hypertension patients. Total antioxidant capacity (TAC), which has a strong relationship with blood pressure, is determined through the ferric reducing antioxidant power (FRAP). The aim of the review article is to elucidate the role of MDA and FRAP in hypertension.Keywords: oxidative stress, hypertension, blood pressure, oxidative damage, malondialdehyde, FRAP